Manganese-free chow, a refined non-invasive solution to reduce gastrointestinal signal for T1-weighted magnetic resonance imaging of the mouse abdomen. (August 2020) - Kersemans, Veerle; Wallington, Sheena; Allen, Philip D; Gilchrist, Stuart; Kinchesh, Paul; Browning, Richard; Vallis, Katherine A; Schilling, Kathrin; Holdship, Phil; Stork, Lee-Anne; Smart, Sean
Commercial mouse chow is designed to provide a complete, nutrient-rich diet, and it can contain upwards of 100 mg/kg manganese, an essential mineral. Manganese acts as a relaxation time-shortening contrast agent for both T1 and T2, and where standard chow is hydrated in the gastrointestinal tract, bright signals are produced when using T1 -weighted imaging (T1 WI). As a result of peristalsis, gastrointestinal hyperintensities result in temporally unstable signals, leading to image ghosting and decreased resolution from that prescribed. To avoid the problem, various methods of gastrointestinal tract modulation, including the use of intestinal cleansing with laxatives and dietary modulation, have been reported. Here, dietary modulation has been extended to the use of a biologically innocuous, long-term change of diet. In this study, we report on the use of a commercially available manganese-free chow to improve the image quality of the gastrointestinal tract. This manganese-free chow, apart from the omitted manganese which is available in tap water, is a complete diet and readily available. We investigated the time-dependent, diet-related gastrointestinal intensities on short-TR T1 WI magnetic resonance imaging; monitored body mass, food and water consumption and standard blood biochemistry analysis following diet change; and determined manganese concentration in blood plasma following a five-day change to manganese-free chow. We show that the manganese-free chow presents a refinement to other gastrointestinal tract modulation, as it avoids the need for invasive procedures for gut voiding and can be provided ad libitum so that animals can be maintained with no need for prescribed diet change before imaging.